A Review of Consanguinity in the Iraqi Population: A Call to Action to Prevent a Future Health Catastrophe - Hawi, Zaid Ali; Pugsley , Kealan; Namipashaki , Atefeh; Samarrai , Wailed; Hawi, Ziarih (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Although not uncommon worldwide, consanguinity has been a part of Arab culture and tradition as a means to strengthen tribal blood relations. However, this type of union has been linked to inherited diseases, particularly those of a recessive nature (e.g., hemoglobinopathies). Furthermore, several recent studies have documented highly significant associations between consanguineous parentage and common multifactorial diseases, including but not limited to hypertension, mental disorders, and several cardiovascular diseases. In Iraq, the prevalence of consanguinity is very high and still on the rise. This has resulted in an increased prevalence of inherited diseases and has significant negative impacts on Iraq’s limited economy. To address this issue, epidemiological studies are urgently required to generate a comprehensive database comprising the distribution of genetically inherited diseases that will be fundamental to establishing an effective future healthcare system. An educational public awareness campaign should accompany these efforts to inform the population about the profound consequences of consanguinity on offspring health. Finally, legislation needs to be put in place to ensure highly vetted genetic testing is conducted prior to any blood-related marriage in order to prevent further genetic complications for future generations of Iraq.